Medical composite hydrogel as well as preparation method and application thereof

The preparation of TMDC/PGS composite materials through hydrothermal method and crosslinked with hydrogels has solved the problems of excessive fluidity and single functionality of existing hydrogel materials, and achieved efficient antibacteriality of medical composite hydrogels, promoting wound healing and improving tissue regeneration capabilities.

CN119770715AActive Publication Date: 2025-04-08TIANJIN JIASHITANG SCI & TECH +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510280959.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-04-08
Estimated Expiration
2045-03-11

AI Technical Summary

Technical Problem

Existing hydrogel materials have problems of excessive fluidity and single functionality in medical dressings, which are difficult to meet the needs of chronic wound repair in patients with complex diseases such as diabetes.

Method used

TMDC/PGS composite material was prepared by hydrothermal method and crosslinked with hydrogel and TSPBA to form a medical composite hydrogel. This method improves the antibacterial properties of the hydrogel, the ability to promote wound healing and tissue regeneration, while enhancing its viscosity and binding strength.

Benefits of technology

It has achieved the improvement of the stability and rheological performance of the hydrogel, enhanced its antibacterial, anti-inflammatory and antioxidant properties, promoted wound healing and tissue regeneration, and is especially suitable for wound repair in diabetic patients.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119770715A_ABST
    Figure CN119770715A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of hydrogel, in particular to medical composite hydrogel as well as a preparation method and application thereof. The preparation method comprises the following steps: compounding attapulgite powder and transition metal sulfide under a high-temperature condition by adopting a hydrothermal method to form a TMDC / PGS composite material; the content of the TMDC in the TMDC / PGS composite material is 90 to 97.5 weight percent; mixing the hydrogel solution with a TSPBA solution to obtain a reaction base solution; and adding the TMDC / PGS composite material into the reaction base solution, and treating under heating and ultrasonic conditions to obtain the medical composite hydrogel. The medical composite hydrogel disclosed by the invention not only has the characteristics of injectability, low toxicity and antibacterial property, but also has the functions of promoting wound healing, promoting epidermis, blood vessel and nerve regeneration, resisting inflammation and resisting oxidation, and is particularly suitable for promoting wound repair of diabetic patients.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogels, and in particular to a medical composite hydrogel and a preparation method and application thereof. Background Art

[0002] Hydrogel materials are a type of polymer material with a three-dimensional network structure that can absorb and retain a large amount of water. Due to its good biocompatibility, excellent flexibility and other properties, hydrogel materials are increasingly used in the field of medical dressings. Hydrogel materials can provide barrier protection for wounds, prevent external bacteria from invading, and reduce the risk of infection. In addition, they can maintain a moist environment on the wound surface and promote wound healing. However, the following problems still exist in the application of hydrogel medical dressings: On the one hand, existing hydrogel materials have the problem of excessive fluidity, which makes it difficult to accurately control when using, affecting the stability and convenience of the dressing. In addition, the bonding strength with the skin is also low, and it is easy to fall off during the patient's activities, resulting in wound exposure and increasing the risk of infection.

[0003] On the other hand, the functionality of existing hydrogel materials is relatively single and it is difficult to meet the needs of patients with more complex conditions. Take the repair of chronic wounds in diabetic patients as an example: Chronic diabetic wound repair is one of the clinical problems that need to be solved urgently. It is generally believed that the reason why chronic diabetic wounds are difficult to heal is due to their unique wound microenvironment: severely unbalanced oxidative stress levels and bacterial infection will aggravate wound hypoxia, inhibit angiogenesis, re-epithelialization and extracellular matrix synthesis, and thus impair the healing process. However, existing hydrogel medical dressings cannot meet the needs of wound recovery, and wounds are often difficult to heal.

[0004] In summary, although the existing hydrogel materials have certain application value in the field of medical dressings, they have obvious deficiencies in fluidity and functionality. How to improve the above properties of hydrogel materials to expand their application in medical dressings has attracted more and more attention from those skilled in the art. Summary of the invention

[0005] In order to solve or partially solve the problems existing in the related art, the present invention provides a medical composite hydrogel and a preparation method and application thereof.

[0006] The present invention provides a method for preparing a medical composite hydrogel, which comprises: Step a), using a hydrothermal method to compound attapulgite powder and transition metal sulfide under high temperature conditions to form a TMDC / PGS composite material; the content of TMDC in the TMDC / PGS composite material is 90-97.5wt%; Step b), mixing the hydrogel solution with the TSPBA solution to obtain a reaction base solution; Step c), adding the TMDC / PGS composite material to the reaction base liquid, and treating it under heating and ultrasonic conditions to obtain a medical composite hydrogel.

[0007] Furthermore, in the step a), the attapulgite powder is prepared according to the following method: The attapulgite is calcined at a temperature of 200-450°C for 2-4 hours at a heating rate of 5-20°C / min. The calcined attapulgite is treated with an acid using a 2-5 mol / L HCl solution for 3-5 h; The acid-treated attapulgite is washed, dried and ground to obtain attapulgite powder.

[0008] Furthermore, the step a) is specifically as follows: Ultrasonic dispersion of attapulgite powder and transition metal sulfide in anhydrous ethanol to obtain a mixed dispersion; in the mixed dispersion, the transition metal sulfide accounts for 90-97.5wt% of the total mass of the attapulgite powder and the transition metal sulfide; The mixed dispersion is subjected to heat treatment at a temperature of 180-260°C, a time of 24-36 hours, and a heating rate of 5-20°C / min; The product obtained after the heat treatment is washed, centrifuged and vacuum dried to obtain a TMDC / PGS composite material.

[0009] Furthermore, in the step b), the concentration of the hydrogel solution is 5-30wt%, the concentration of the TSPBA solution is 5-30wt%; and the mixing volume ratio of the hydrogel solution to the TSPBA solution is 1-5:1.

[0010] Furthermore, in the step c), the mixing ratio of the TMDC / PGS composite material and the reaction base liquid is 1-5 mg:1 mL.

[0011] Furthermore, in the step c), the heating is water bath heating at a temperature of 70-90° C. for a time of 10-30 min.

[0012] Further, the hydrogel solution is a polyvinyl alcohol solution, an alginate solution, a chitosan solution, a gelatin solution, a hyaluronic acid solution, a polyethylene glycol solution, a polyacrylamide solution, a carboxymethyl cellulose solution or a methyl cellulose solution; and / or, The transition metal sulfide is MoS2.

[0013] Furthermore, the content of TMDC in the TMDC / PGS composite material is 92.5-95wt%.

[0014] The invention also provides a medical composite hydrogel, which comprises: a TSPBA modified high molecular polymer, a TMDC / PGS composite material, and water.

[0015] Furthermore, the medical dressing has at least one of the following functions: promoting wound healing, promoting epidermal, blood vessel and nerve regeneration, antibacterial, anti-inflammatory and anti-oxidative.

[0016] The medical composite hydrogel and preparation method thereof provided by the present invention may have the following beneficial effects: 1) The present invention first prepares a TMDC / PGS composite material by a hydrothermal method, and finally cross-links HG, TSPBA and the TMDC / PGS composite material to form a medical composite hydrogel. HG is modified by cross-linking the boric acid bond of TSPBA and the hydroxyl group of HG to form a borate ester bond, thereby forming an optimized hydrogel, which better plays a physical barrier role and increases the ability to inhibit oxidative stress. Compounding TMDC and PGS can not only increase the specific surface area of ​​TMDC, improve its absorbance, enhance the photothermal reaction and photodynamic reaction ability, but also reduce the toxicity of the material. Therefore, the introduction of TMDC / PGS composite material enhances the antibacterial properties of hydrogels, while promoting the functions of wound epidermal regeneration and vascular reconstruction / endowing hydrogels with stable physical properties such as viscosity and elasticity.

[0017] 2) The method of the present invention can construct an oxidative microenvironment and a photodynamic antibacterial dual-control intelligent inorganic / organic hybrid hydrogel, synergistically exerting the advantages of inorganic and organic materials, and can simultaneously solve the two key problems of bacterial infection and oxidative stress that affect the healing of chronic wounds; the wound microenvironment can be controllably adjusted by controlling the duration of light exposure according to the wound condition, which has important clinical value in promoting the regeneration of skin on chronic difficult-to-heal wounds. In addition, the prepared composite hydrogel is injectable and can form gel in situ at the wound site, effectively isolating the wound from the environment and reducing the risk of infection; at the same time, for wounds with susceptible characteristics such as diabetic wounds, the TMDC / PGS composite material in the gel can be controllably and efficiently antibacterial, and finally the combination of the two can achieve the treatment of complex wounds such as diabetes.

[0018] 3) Experiments have shown that the medical composite hydrogel prepared by the present invention not only has the characteristics of injectability, low toxicity and antibacterial properties, but also has the functions of promoting wound healing, promoting epidermal, blood vessel and nerve regeneration, anti-inflammatory and antioxidant functions, and is particularly suitable for promoting the repair of wounds in diabetic patients.

[0019] It is to be understood that both the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention in conjunction with the accompanying drawings, wherein like reference numerals generally represent like components throughout the exemplary embodiments of the present invention.

[0021] Figure 1 is a physical picture of the injectability test in the embodiment of the present invention; Figure 2 is a physical picture of the rheological visibility experiment in the embodiment of the present invention; Figure 3 is a graph showing the relationship between temperature and time of four medical composite hydrogels in an embodiment of the present invention; Figure 4 is a graph showing the relationship between viscosity and time of four medical composite hydrogels in the embodiments of the present invention; Figure 5 is a scanning electron microscope image of the medical composite hydrogel in a completely cured state corresponding to Example 3 of the present invention; Figure 6 is a graph showing the inorganic element ratio of the medical composite hydrogel in a completely cured state corresponding to Example 3 of the present invention; Figure 7 is a physical photograph of the mechanical elasticity test in the embodiment of the present invention; Figure 8 is a microscope image of a cell scratch experiment in an embodiment of the present invention; Fig. 9 It is a fluorescent staining image of the cell live-death experiment / cytotoxicity test in the embodiment of the present invention. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The singular forms "a", "the" and "the" used in the present invention and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.

[0024] It should be understood that although the terms "first", "second", "third", etc. may be used to describe various information in the present invention, such information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of the present invention, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.

[0025] The present invention provides a method for preparing a medical composite hydrogel, which comprises the following steps: Step a), using a hydrothermal method to compound attapulgite powder and transition metal sulfide under high temperature conditions to form a TMDC / PGS composite material; the content of TMDC in the TMDC / PGS composite material is 90-97.5wt%; Step b), mixing the hydrogel solution with the TSPBA solution to obtain a reaction base solution; Step c), adding the TMDC / PGS composite material to the reaction base liquid, and treating it under heating and ultrasonic conditions to obtain a medical composite hydrogel.

[0026] The inventive concept of this application is as follows: N1- (4-bromobenzyl)-N3- (4-bromophenyl)-N1,N1,N3,N3-tetramethylpropane-1,3-diamine TSPBA was used as a crosslinker to crosslink with hydrogel HG (such as PVA, etc.). TSPBA is a compound containing a methacryloyloxy group and a phenolic structure, which is polymerizable and crosslinkable. Its phenylboronic acid functional group can also give the material molecular recognition and response capabilities. During the crosslinking reaction, the boric acid bond of TSPBA and the hydroxyl group of HG are crosslinked to form a boric acid ester bond to modify HG, thereby forming an optimized hydrogel HG-TSPBA, which increases the stability and rheological properties of the hydrogel. In addition, due to the introduction of TSPBA, the hydrogel not only has the original biocompatibility and water solubility, but also increases the ability to inhibit oxidative stress response.

[0027] On this basis, the inventors of the present application further considered compounding other functional materials for modification to give the hydrogel more properties, such as antibacterial and antioxidant properties, so that it can be applied to more patients' wound repair. For the selection of functional materials, the inventors of the present application first considered the use of transition metal sulfide TMDC. As a classic light absorber, TMDC kills bacteria through photothermal reaction and photodynamic reaction, is used in the treatment of infected wounds, and has good biocompatibility. However, the inventors of the present application found through research that the compounding of TMDC with the hydrogel HG-TSPBA has the problem of high toxicity. In addition, its effect on improving antibacterial and antioxidant properties is not ideal, and the wound healing ability and angiogenesis ability also need to be improved.

[0028] In order to improve the above problems, the present application considers adding other functional composite materials, but the effects are not ideal. Then the inventor of the present application found through research that after compounding TMDC with attapulgite PGS and then compounding with hydrogel HG-TSPBA, not only the above problems can be solved, but also better viscosity can be given to the hydrogel, and the bonding strength with the wound tissue can be improved. Specifically: attapulgite PGS is also a kind of nanomaterial, which is abundant in my country, with rich resources, low price and convenient material acquisition. Among them, SiO2 is the main material, and SiO2 has a "needle tip" morphology, which can kill bacteria adhering to the surface and inhibit bacterial reproduction. Moreover, after PGS is compounded with TMDC, the specific surface area of ​​TMDC can be increased, its absorbance can be improved, and the photothermal reaction and photodynamic reaction ability can be enhanced. In addition, the toxicity of the material can be reduced. Attapulgite also has rheological properties. When attapulgite encounters water, it can swell and disperse rapidly to form an irregular fiber network, and finally form a high viscosity and high stability dispersion with rheological properties. Therefore, the introduction of attapulgite also increases the viscosity of the hydrogel system.

[0029] On this basis, the TMDC / PGS composite material was uniformly dispersed in HG and TSPBA and then cross-linked to obtain a medical composite hydrogel.

[0030] The above step a) is a step of preparing a TMDC / PGS composite material using attapulgite powder and transition metal sulfide as raw materials. The inventors have found through research that the ratio of the two materials in the TMDC / PGS composite material has an impact on the rheological properties, antibacterial properties, and tissue repair properties of the final medical composite hydrogel. When the content of TMDC in the TMDC / PGS composite material is 90-97.5wt%, the performance of the obtained medical composite hydrogel is better.

[0031] This step is preferably as follows: Ultrasonic dispersion of attapulgite powder and transition metal sulfide in anhydrous ethanol to obtain a mixed dispersion; in the mixed dispersion, the transition metal sulfide accounts for 90-97.5wt% of the total mass of the attapulgite powder and the transition metal sulfide; The mixed dispersion is subjected to heat treatment at a temperature of 180-260°C, a time of 24-36 hours, and a heating rate of 5-20°C / min; The product obtained after the heat treatment is washed, centrifuged and vacuum dried to obtain a TMDC / PGS composite material.

[0032] Ultrasonic dispersion of attapulgite powder and transition metal sulfide in anhydrous ethanol can ensure that the two materials are evenly mixed to form a stable mixed dispersion. Ultrasonic dispersion helps to break up agglomerations and better disperse the powder. The attapulgite powder and transition metal sulfide can be dispersed in anhydrous ethanol separately, and then the two dispersions are mixed in proportion; or the attapulgite powder and transition metal sulfide can be mixed in proportion first and then dispersed in anhydrous ethanol.

[0033] After obtaining the mixed dispersion, hydrothermal compounding is performed. The high temperature condition can promote the interaction between attapulgite and transition metal sulfide, thereby enhancing the structural stability of the composite material. At the same time, heat treatment also helps to remove the solvent and promote the curing of the material. The condition temperature of the heat treatment is more preferably: temperature 200-230°C, time 2-3h, heating rate 8-12°C / min. The condition temperature of the heat treatment is most preferably: temperature 300°C, time 2h, heating rate 10°C / min.

[0034] After heat treatment, the product is washed and centrifuged to remove impurities such as solvents that may remain during the reaction process; vacuum drying is to remove moisture from the composite material, while isolating oxygen to prevent the occurrence of side reactions, and finally obtaining a dry TMDC / PGS composite material.

[0035] The attapulgite powder used in this step is preferably prepared as follows: The attapulgite is calcined at a temperature of 200-450°C for 2-4 hours at a heating rate of 5-20°C / min. The calcined attapulgite is treated with an acid using a 2-5 mol / L HCl solution for 3-5 h; The acid-treated attapulgite is washed, dried and ground to obtain attapulgite powder.

[0036] After heat treatment, attapulgite has strong adsorption properties and thermal stability. In addition, calcining attapulgite can remove organic matter, moisture and other volatile impurities therein, thereby purifying the material. In addition, calcination can also change the crystal structure and surface properties of attapulgite, improve its activity and surface area, and expand its pore size, thereby improving its adsorption capacity and cation exchange capacity, which is beneficial to subsequent acid treatment and composite with transition metal sulfides. The calcination temperature is more preferably 290-320°C, the time is more preferably 2-3h, and the heating rate is more preferably 8-12°C / min. Most preferably, the calcination temperature is 300°C, the time is 2h, and the heating rate is 10°C / min.

[0037] Subsequent acid treatment can remove metal oxides and other impurities on the surface and inside the voids of attapulgite, increase its surface active sites, and thus improve its ability to bind to transition metal sulfides. The concentration of the HCl solution is more preferably 2 mol / L, and the treatment time is more preferably 3 h. In order to improve the treatment efficiency, this step is preferably carried out under stirring.

[0038] After the acid treatment, the attapulgite is washed to remove the hydrochloric acid remaining in the attapulgite, and dried to remove the moisture; the attapulgite is ground to obtain a powdered attapulgite, which increases the specific surface area and is conducive to the composite with the transition metal sulfide.

[0039] Step b) is a step of mixing the hydrogel solution with the TSPBA solution to obtain a reaction base liquid, which provides a basic matrix and reaction environment for the subsequent preparation of the composite hydrogel. In this step, the concentration of the hydrogel solution is preferably 5-30wt%, and the concentration of the TSPBA solution is preferably 5-30wt%; the mixing volume ratio of the hydrogel solution and the TSPBA solution is 1-5:1. It can be understood by those skilled in the art that the solvents of the hydrogel solution and the TSPBA solution are both water. The ratio of TMDC / PGS composite material, HG and TSPBA has an impact on the rheological properties of the final composite gel and the functions of antibacterial promotion of tissue repair. Further, the mixing ratio of the TMDC / PGS composite material and the reaction base liquid is 1-5mg:1mL.

[0040] TSPBA can be prepared by a precipitation method, specifically: 4-(bromomethyl)phenylboronic acid and tetramethylpropylenediamine are used as reactants, react in DMF under heating conditions, and after the reaction is complete, tetrahydrofuran is added to the reaction system to promote product precipitation, and the solid product is separated and washed and dried to obtain TSPBA. The molar ratio of 4-(bromomethyl)phenylboronic acid to tetramethylpropylenediamine is preferably 1-6:1, and the heating temperature is preferably 45-70°C. Most preferably, the molar ratio of 4-(bromomethyl)phenylboronic acid to tetramethylpropylenediamine is preferably 3-3.1:1, and the heating temperature is preferably 60°C.

[0041] Step c) is a step of mixing the TMDC / PGS composite material with a reaction base liquid and treating it under heating and ultrasonic conditions to prepare a medical composite hydrogel. Heating can promote the cross-linking reaction and help improve the uniformity of the dispersion of the TMDC / PGS composite material in the hydrogel matrix. The heating method is preferably water bath heating, the heating temperature is preferably 70-90°C, and the time is preferably 10-30min. Most preferably, the heating temperature is 90°C and the time is 15min. Ultrasonic treatment can enhance the dispersibility of the TMDC / PGS composite material in the reaction base liquid, reduce agglomeration, and promote uniform mixing. In addition, ultrasound can also generate local high temperature and high pressure through cavitation, further promoting the chemical reaction.

[0042] The material of the hydrogel HG is preferably polyvinyl alcohol, alginate, chitosan, gelatin, hyaluronic acid, polyethylene glycol, polyacrylamide, carboxymethyl cellulose or methyl cellulose; and / or, the transition metal sulfide TMDC is MoS2. Further preferably, the material of the hydrogel HG is PVA, and TMDC is MoS2. In this case, the content of MoS2 in the TMDC / PGS composite material is preferably 92.5-95wt%, the concentration of the PVA solution is preferably 13-16wt%, the concentration of the TSPBA solution is preferably 4-6wt%, the mixing volume ratio of the PVA solution to the TSPBA solution is preferably 2-4:1, and the mixing ratio of the TMDC / PGS composite material and the reaction base liquid is preferably 4-5mg:1mL. Most preferably, the content of MoS2 in the TMDC / PGS composite material is 92.5wt%, the concentration of the PVA solution is 15wt%, the concentration of the TSPBA solution is preferably 3wt%, the mixing volume ratio of the PVA solution and the TSPBA solution is 3:1, and the mixing ratio of the TMDC / PGS composite material and the reaction base liquid is 5mg:1mL.

[0043] Step c) A uniform and stable medical composite hydrogel TMDC / PGS@HG-TSPBA can be obtained by ultrasonic and heating treatment, wherein the TMDC / PGS composite material is uniformly distributed in the hydrogel HG-TSPBA, giving the hydrogel better rheological properties, higher bonding strength with tissues, and better tissue regeneration, antibacterial, anti-inflammatory and antioxidant properties.

[0044] Step c) The composite hydrogel obtained after heating has good fluidity. After being placed at room temperature for a period of time, the hydrogel continues to solidify, the fluidity weakens, and the adhesion is enhanced. Those skilled in the art can select the specific application mode of the composite hydrogel according to actual needs. For example, if it is used for injection, it can be taken out for injection immediately after heating. At this time, the composite hydrogel has good fluidity, which is convenient for filling and injection. After the injection is completed, wait for 10-20 minutes for the composite hydrogel to be completely solidified and firmly adhere to the wound surface. If it is used for non-injection purposes such as plasters, it can be taken out after heating and left to stand for 10-20 minutes, and then attached to the wound surface after the composite hydrogel is completely solidified.

[0045] Another embodiment of the present invention also provides a medical composite hydrogel, comprising: TSPBA modified polymer, TMDC / PGS composite material, and water. It can be prepared according to the method described in the above embodiment. The medical composite hydrogel has the following advantages: The medical composite hydrogel has excellent rheological properties, is injectable, has high adhesion strength with the epidermis, heart, liver and other organs, can deform accordingly with the deformation of the attached object, and is not easy to fall off; The medical composite hydrogel has low toxicity and mild use conditions; The medical composite hydrogel has excellent antibacterial, anti-inflammatory and antioxidant properties. In addition, it also has a good effect on promoting tissue healing and angiogenesis.

[0046] Another embodiment of the present invention also provides an application of the above-mentioned medical composite hydrogel in a medical dressing, wherein the medical dressing has at least one of the following functions: promoting wound healing, promoting epidermal, blood vessel and nerve regeneration, antibacterial, anti-inflammatory and anti-oxidative. It is particularly suitable for use in promoting wound repair in diabetic patients.

[0047] It can be seen from the above content that the medical composite hydrogel and the preparation method thereof provided by the embodiments of the present invention have the following advantages: 1) The present invention first prepares a TMDC / PGS composite material by a hydrothermal method, and finally cross-links HG, TSPBA and the TMDC / PGS composite material to form a medical composite hydrogel. HG is modified by cross-linking the boric acid bond of TSPBA and the hydroxyl group of HG to form a borate ester bond, thereby forming an optimized hydrogel, which better plays a physical barrier role and increases the ability to inhibit oxidative stress response. Compounding TMDC and PGS can not only increase the specific surface area of ​​TMDC, but also increase its absorbance, enhance the photothermal reaction and photodynamic reaction capabilities, and can also reduce the toxicity of the material. Therefore, the introduction of the TMDC / PGS composite material not only improves the antibacterial properties of the hydrogel, but also reduces the toxicity of the material.

[0048] 2) The method of the present invention can construct an oxidative microenvironment and a photodynamic antibacterial dual-control intelligent inorganic / organic hybrid hydrogel, synergistically exerting the advantages of inorganic and organic materials, and can simultaneously solve the two key problems of bacterial infection and oxidative stress that affect the healing of chronic wounds; the wound microenvironment can be controllably adjusted by controlling the duration of light exposure according to the wound condition, which has important clinical value in promoting the regeneration of skin on chronic difficult-to-heal wounds. In addition, the prepared composite hydrogel is injectable and can form gel in situ at the wound site, effectively isolating the wound from the environment and reducing the risk of infection; at the same time, for wounds with susceptible characteristics such as diabetic wounds, the TMDC / PGS composite material in the gel can be controllably and efficiently antibacterial, and finally the combination of the two can achieve the treatment of complex wounds such as diabetes.

[0049] 3) Experiments have shown that the medical composite hydrogel prepared by the present invention not only has the characteristics of injectability, low toxicity and antibacterial properties, but also has the functions of promoting wound healing, promoting epidermal, blood vessel and nerve regeneration, antibacterial, anti-inflammatory and antioxidant, and is particularly suitable for promoting the repair of wounds in diabetic patients.

[0050] The technical solution of the present invention is further described below in conjunction with specific embodiments: The MoS2 in the following embodiments are all M888682 nano molybdenum disulfide purchased from McLean Company, with the specifications of: ≥99.5%, 100nm, cas: 1317-33-5.

[0051] The attapulgite in the following examples was purchased from Jiangsu Xuyi Attapulgite Co., Ltd.

[0052] The TSPBA in the following examples were prepared as follows: 9.2mmol 4-(bromomethyl)phenylboronic acid and 3mmol tetramethylpropylenediamine (TMPA) were placed in a 100mL round-bottom flask, 40mL N,N-dimethylformamide (DMF) was added thereto, and the temperature of the reaction system was adjusted to 60℃ for overnight reaction. After the reaction was completed, the reaction system was cooled to room temperature, 400mL tetrahydrofuran was added to the system, and white solid was precipitated. Filtered with a sand core funnel, washed with 240mL tetrahydrofuran three times, and then the filter cake was collected and placed in a vacuum drying oven for drying to obtain TSPBA.

[0053] The attapulgite powder PGS in the following examples were prepared according to the following method: Put attapulgite into a clean ceramic crucible, cover it, and place it in the center of a muffle furnace. Heat it at a heating rate of 10 °C / min to 300 °C, and conduct heat treatment for 2 h. After the temperature drops to room temperature, take it out. Add the calcined attapulgite to the prepared 3 mol / L HCl solution, continuously stir for 3 h. After the reaction ends, centrifuge and separate the attapulgite, and wash it with deionized water multiple times until the pH is neutral. Finally, dry it in an oven at 60 °C for 8 h and grind it into powder to obtain the completely heat-treated and acid-treated attapulgite powder PGS.

[0054] Example 1 1). Preparation of MoS2 / PGS composite material: Dissolve PGS and MoS2 separately in 20 ml of absolute ethanol, and conduct ultrasonic treatment to make them completely dispersed. Mix the dispersion liquids and stir well. The percentage M1 of PGS in the total solid mass (the total mass of PGS and MoS2) in the mixed dispersion liquid is 2.5%, and the percentage M2 of MoS2 in the total solid mass (the total mass of PGS and MoS2) is 97.5%; Add the mixed dispersion liquid to a 100 mL reaction kettle, and keep it at 220 °C in a muffle furnace for 24 hours. After the product is washed and centrifuged and separated multiple times, it is freeze-dried for standby.

[0055] 2). Preparation of composite hydrogel: Take 397.2 mg of PVA and place it in 2.25 mL of deionized water to prepare a 15 wt% PVA aqueous solution. Then take 39.6 mg of TSPBA and place it in 0.75 ml of deionized water to prepare a 5 wt% TSPBA aqueous solution. Mix the PVA aqueous solution and the TSPBA aqueous solution in a volume ratio of 3:1 to obtain a reaction base liquid; Add 15 mg of the MoS2 / PGS composite material prepared in step 1) to the reaction base liquid, place it in a 90 °C water bath, and heat it for 15 min to form 3 ml of PVA-TSPBA@PGS / MoS2 medical composite hydrogel.

[0056] Examples 2 - 4 The difference from Example 1 is in step 1): The percentage M1 of PGS in the total solid mass and the percentage M2 of MoS2 in the total solid mass in the mixed dispersion liquid are different. The M1 and the percentage M2 of TMDC in the total solid mass of Examples 1 - 4 are listed in Table 1: Table 1 Contents of M1 and M2 in Examples 1 - 4

[0057]

Injectability test

[0058] Depend on Figure 1 It can be seen that the medical composite hydrogels prepared in Examples 1-4 are all injectable, and the composite hydrogels in Examples 2 and 3 have the best injectable properties.

[0059]

Rheological visibility experiment

[0060] Depend on Figure 2 It can be seen that the medical composite hydrogel material has fluidity in the early stage, gradually becomes sticky during the gelation process, and finally becomes a colloid with strong adhesion.

[0061] The composite hydrogels corresponding to Examples 1-4 are labeled as follows: Example 1: 2.5% PGS / 97.5% MoS2@PVA-TSPBA; Example 2: 5% PGS / 95% MoS2@PVA-TSPBA; Example 3: 7.5% PGS / 92.5% MoS2@PVA-TSPBA; Example 4: 10%PGS / 90%MoS2@PVA-TSPBA The above four materials were subjected to photothermal performance test, rheological performance test, qualitative analysis, mechanical elasticity test and organ viscosity test. The details are as follows:

Photothermal performance test

[0062]

Rheological properties test

[0063] 2. Take the initial state medical composite hydrogel prepared in Examples 1-4, and test the relationship between its storage modulus G' and loss modulus G'' and time. The storage modulus is greater than the loss modulus, indicating that the sample is more solid and elastic; the loss modulus is greater than the storage modulus, indicating that the sample is more liquid and injectable. The test results are as follows: The viscosity of the four medical composite hydrogel materials changes with time, and all change from liquid to solid. The time of the transformation of the medical composite hydrogel corresponding to Example 3 is moderate.

[0064] From the above content, it can be seen that among the four medical composite hydrogel materials, the medical composite hydrogel corresponding to Example 3 has the best rheological properties, is injectable in the early stage, meets the experimental injectable operation, has solid viscoelasticity in the later stage, and is not easy to deform or lose after covering the wound.

[0065] [Qualitative analysis] 1. Morphology analysis: Figure 5 The scanning electron microscope image of the medical composite hydrogel in the fully cured state corresponding to Example 3 is shown. Figure 5 It can be seen that the morphology of the finished medical composite hydrogel material is porous.

[0066] 2. Analysis of inorganic components: The inorganic element ratio of the medical composite hydrogel in the fully cured state corresponding to Example 3 is shown in FIG. Figure 6 shown.

[0067] Depend on Figure 6 It can be seen that the main elements in the inorganic components of the medical composite hydrogel are Mo, S, Si, and O. The element ratio is accurate and evenly distributed, indicating that PGS / MoS2 in the finished material is successfully prepared.

[0068]

Mechanical elasticity test

[0069] Depend on Figure 7 It can be seen that the medical composite hydrogel corresponding to Example 3 has good adhesion, elasticity and mobility at the joints.

[0070]

Organ viscosity test

[0071] The following comparative examples are used to compare the performance of the medical composite hydrogel prepared in the examples of the present application in terms of application: Comparative Example 1 397.2 mg of PVA was placed in 2.25 mL of deionized water to prepare a 15 wt% PVA aqueous solution, and 39.6 mg of TSPBA was placed in 0.75 mL of deionized water to prepare a 5 wt% TSPBA aqueous solution. The PVA aqueous solution and the TSPBA aqueous solution were mixed in a volume ratio of 3:1 to obtain a reaction base solution; The reaction base liquid was placed in a 90°C water bath and heated for 15 minutes to form 3 ml of medical hydrogel.

[0072] Comparative Example 2 397.2 mg of PVA was placed in 2.25 mL of deionized water to prepare a 15 wt% PVA aqueous solution, and 39.6 mg of TSPBA was placed in 0.75 mL of deionized water to prepare a 5 wt% TSPBA aqueous solution. The PVA aqueous solution and the TSPBA aqueous solution were mixed in a volume ratio of 3:1 to obtain a reaction base solution; Add 13.8 mg of MoS2 to the reaction base liquid, place it in a 90°C water bath, and heat it for 15 minutes to form 3 ml of medical composite hydrogel.

[0073] The hydrogels corresponding to Example 3, Comparative Example 1 and Comparative Example 2 were labeled as follows: Example 3: PVA-TSPBA@MoS2 / PGS; Comparative Example 1: PVA-TSPBA Comparative Example 2: PVA-TSPBA@MoS2 The medical composite hydrogel prepared in Example 3, the medical composite hydrogel prepared in Comparative Example 1 and the medical composite hydrogel prepared in Comparative Example 2 were placed at room temperature for 18-20 minutes and completely cured, and then the following analysis and performance comparison tests were performed:

Organic component analysis

[0074]

Cell scratch test

[0075] Depend on Figure 8 It can be seen that compared with Comparative Examples 1 and 3, the medical composite hydrogel material corresponding to Example 3 has obvious cells spread in the scratch area after 36 hours, showing a significant ability to promote wound healing.

[0076]

Cell live / death experiment / cytotoxicity test

[0077] Depend on Fig. 9 It can be seen that: in the PVA-TSPBA group hydrogel material, there are more surviving cells and fewer dead cells, showing low cytotoxicity; in the PVA-TSPBA@MoS2 group hydrogel material, the number of surviving cells is significantly reduced, and the number of dead cells is significantly increased, showing high cytotoxicity; in the PVA-TSPBA@MoS2 / PGS group hydrogel material, there are more surviving cells and fewer dead cells, indicating that after PGS is added to the material, the cytotoxicity of PVA-TSPBA@MoS2 / PGS is reduced and modified.

[0078]

Antioxidant Experiment

[0079]

Antibacterial test

[0080]

Wound healing experiment

[0081] The wound surfaces of four groups of diabetic mice were applied with normal saline (control group) and three groups of hydrogel materials respectively.

[0082] The observation time points were set as 0 days, 3 days, 7 days, 10 days, 12 days, and 14 days, and the changes in the wound surface at each time point were recorded.

[0083] On the third day, secretion samples were collected from the wound surface. The secretion samples were inoculated into the culture medium for bacterial culture and the growth of bacteria was observed. After 24 hours, the bacterial growth was as follows: The antibacterial effect of Example 1 group was significantly better than that of the other three groups.

[0084] On the 14th day, wound tissues were taken for HE pathological staining, Masson pathological staining and immunofluorescence. On the 14th day, the heart, liver, spleen, lung and kidney organs of the mice were taken for pathological examination. The test results are as follows: The PVA-TSPBA@MoS2 / PGS group hydrogel material promoted the healing of infected wounds in diabetic mice best.

[0085] The PVA-TSPBA@MoS2 / PGS group hydrogel material has the best antibacterial effect on infected wounds in diabetic mice.

[0086] In the PVA-TSPBA@MoS2 / PGS group of hydrogel materials, wound scar healed, keratinocytes were visible in the epidermis, and collagen deposition was visible under the epidermis, indicating that this material promoted the healing of infected wounds in diabetic mice best; in the PVA-TSPBA@MoS2 group of hydrogel materials, epidermal healing trends were observed, and a large amount of granulation tissue was regenerated; in the PVA-TSPBA group of hydrogel materials, scab formation was observed, and necrotic tissue and secretions were present under the scab; in the Control group, scab formation was observed, and a large amount of necrotic tissue and secretions were present under the scab.

[0087] It can be seen that the PVA-TSPBA@MoS2 / PGS group hydrogel material has the highest fluorescence signals of epidermis, blood vessels and nerves, indicating that it has the strongest ability to promote the regeneration of epidermis, blood vessels and nerves.

[0088] All three hydrogel materials have no obvious organ toxicity, indicating that their biosafety is reliable.

[0089] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A method for preparing a medical composite hydrogel, characterized in that: include: Step a), using a hydrothermal method to compound attapulgite powder and transition metal sulfide under high temperature conditions to form a TMDC / PGS composite material; The content of TMDC in the TMDC / PGS composite material is 90-97.5wt%; Step b), mixing the hydrogel solution with the TSPBA solution to obtain a reaction base solution; Step c), adding the TMDC / PGS composite material to the reaction base liquid, and treating it under heating and ultrasonic conditions to obtain a medical composite hydrogel.

2. The preparation method according to claim 1, characterized in that: In the step a), the attapulgite powder is prepared according to the following method: The attapulgite is calcined at a temperature of 200-450°C for 2-4 hours at a heating rate of 5-20°C / min. The calcined attapulgite is treated with an acid using a 2-5 mol / L HCl solution for 3-5 h; The acid-treated attapulgite is washed, dried and ground to obtain attapulgite powder.

3. The preparation method according to claim 1, characterized in that: The step a) is specifically as follows: Ultrasonic dispersion of attapulgite powder and transition metal sulfide in anhydrous ethanol to obtain a mixed dispersion; in the mixed dispersion, the transition metal sulfide accounts for 90-97.5wt% of the total mass of the attapulgite powder and the transition metal sulfide; The mixed dispersion is subjected to heat treatment at a temperature of 180-260°C, a time of 24-36 hours, and a heating rate of 5-20°C / min; The product obtained after the heat treatment is washed, centrifuged and vacuum dried to obtain a TMDC / PGS composite material.

4. The preparation method according to claim 1, characterized in that: In the step b), the concentration of the hydrogel solution is 5-30wt%, and the concentration of the TSPBA solution is 5-30wt%; the mixing volume ratio of the hydrogel solution to the TSPBA solution is 1-5:

1.

5. The preparation method according to claim 4, characterized in that: In the step c), the mixing ratio of the TMDC / PGS composite material and the reaction base liquid is 1-5 mg:1 mL.

6. The preparation method according to claim 1, characterized in that: In the step c), the heating is carried out in a water bath at a temperature of 70-90° C. for a time of 10-30 min.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The hydrogel solution is a polyvinyl alcohol solution, an alginate solution, a chitosan solution, a gelatin solution, a hyaluronic acid solution, a polyethylene glycol solution, a polyacrylamide solution, a carboxymethyl cellulose solution or a methyl cellulose solution; and / or, The transition metal sulfide is MoS2.

8. The preparation method according to claim 7, characterized in that: The content of TMDC in the TMDC / PGS composite material is 92.5-95wt%.

9. A medical composite hydrogel, characterized in that: include: TSPBA modified polymer, TMDC / PGS composites, and water.

10. Use of the medical composite hydrogel according to claim 9 in medical dressings, characterized in that: The medical dressing has at least one of the following functions: promoting wound healing, promoting epidermal, blood vessel and nerve regeneration, antibacterial, anti-inflammatory and anti-oxidative.

Citation Information

Patent Citations

  • Preparation method and application of attapulgite / molybdenum sulfide composite material

    CN106824229A

  • Preparation method of modified attapulgite loaded sulfurized nano zero-valent iron heavy metal adsorbent, product and application

    CN113457617A

  • Silver sulfide / molybdenum disulfide / acidified attapulgite nano-composite light-driven antibacterial material as well as preparation method and application thereof

    CN113841708A

  • Preparation method and application of modified attapulgite loaded ferrous sulfide

    CN114377647A

  • High-activity and high-yield attapulgite compound enzyme as well as preparation method and application thereof

    CN116603543A